COVID-19 Fatality: Statistical Evidence to Engender the Need for Focal Shift from Air Pollutants to Multi-dimensional Intervention - Satya S. Patra; Subhasmita Panda; Trupti Das; Boopathy Ramasamy (Aerosol and Air Quality Research)
Abstract Since the outbreak of COVID-19 pandemic, several researchers worldwide have suggested chronic exposure to air pollutants viz. PM2.5, NO2, and O3 as one of the influencing factors for the increased rate of fatality. However, most of these studies lacked a comprehensive international outlook. A strong correlation on a regional scale might require further investigations to evaluate the transboundary validity. Therefore, the current study aims to explore the statistical soundness of association of COVID-19 fatality with PM2.5, NO2, and O3 concentration levels across 463 air quality monitoring stations located in 35 selected cities from USA, India and European Regions (France, Germany and Italy). An aggregated open-source air quality data source was used to download the PM2.5, NO2, and O3 concentration for > 900 days in the selected cities. The median of this long-term exposure was tested against the COVID-19 fatality rates. A strength of association parameter, ω2, and the coefficient of determination, R2, were used to evaluate the transboundary association. ω2 results indicated that only 24.6%, 0.03% and 15.4% of the variation in COVID-19 fatality rates could be explained using PM2.5, NO2, and O3 concentrations respectively for all the analyzed cities. Further, low values of R2 between pollutant concentrations and COVID-19 fatality rates corroborated the results (0.27 for PM2.5, 0.00038 for NO2 and 0.18 for O3). These observations strongly suggest a focal shift towards the inclusion of more explanatory variables and an extensive multi-disciplinary work is required in order to understand the cause of COVID-19 fatality.